Cover Image, Volume 26, Issue 4. (25th March 2018) - Chavali, Raghu V. K.; De Wolf, Stefaan; Alam, Muhammad A.
Abstract : The cover image, by Raghu V. K. Chavali et al., is based on the Research Article Device physics underlying silicon heterojunction and passivating‐contact solar cells: A topical review, DOI:10.1002/pip.2959 . Image Credit: Research Publication Services, King Abdullah University of Science and Technology.